Topoisomerase 1 inhibits MYC promoter activity by inducing G-quadruplex formation. Issue 11 (10th June 2022) - Keller, Josephine Geertsen; Hymøller, Kirstine Mejlstrup; Thorsager, Maria Eriksen; Hansen, Noriko Y; Erlandsen, Jens Uldum; Tesauro, Cinzia; Simonsen, Anne Katrine W; Andersen, Anne Bech; Vandsø Petersen, Kamilla; Holm, Lise Lolle; Stougaard, Magnus; Andresen, Brage Storstein; et al.
Abstract: We have investigated the function of human topoisomerase 1 (TOP1) in regulation of G-quadruplex (G4) formation in the Pu27 region of the MYC P1 promoter. Pu27 is among the best characterized G4 forming sequences in the human genome and it is well known that promoter activity is inhibited upon G4 formation in this region. We found that TOP1 downregulation stimulated transcription from a promoter with wildtype Pu27 but not if the G4 motif in Pu27 was interrupted by mutation(s). The effect was not specific to the MYC promoter and similar results were obtained for the G4 forming promoter element WT21. The other major DNA topoisomerases with relaxation activity, topoisomerases 2α and β, on the other hand, did not affect G4 dependent promoter activity. The cellular studies were supported by in vitro investigations demonstrating a high affinity of TOP1 for wildtype Pu27 but not for mutant sequences unable to form G4. Moreover, TOP1 was able to induce G4 formation in Pu27 inserted in double stranded plasmid DNA in vitro . This is the first time TOP1 has been demonstrated capable of inducing G4 formation in double stranded DNA and of influencing G4 formation in cells.